Preventing Unplanned Perioperative Hypothermia in Children. (31st January 2017) - Beedle, Susan E.; Phillips, Amy; Wiggins, Shirley; Struwe, Leeza
Abstract: Unplanned perioperative hypothermia is a common surgical risk. Unplanned hypothermia is defined as a body temperature below 36° C (96.8° F) during any phase of the perioperative period. Perioperative nurses at a Midwestern tertiary pediatric hospital developed an evidence‐based clinical practice guideline (CPG) designed to maintain normothermia for the pediatric surgical population. This CPG outlined standard thermoregulation nursing interventions and required the consistent use of a temporal artery thermometer. A test of this CPG before full implementation established a baseline incidence of unplanned hypothermia at 16.3% (n = 80). The purpose of this study was to measure the rate of perioperative hypothermia in children after implementing the evidence‐based CPG. The study results demonstrated that the CPG, guiding research‐based nursing practice, consistently prevented unplanned hypothermia. The incidence rate of unplanned perioperative hypothermia after CPG implementation was 1.84% (n = 1, 196).